2012
DOI: 10.2147/jep.s35326
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nootropic drugs with cholinergic activity in treatment of cognitive deficit: a review

Abstract: Nootropics represent probably the first “smart drugs” used for the treatment of cognitive deficits. The aim of this paper is to verify, by a systematic analysis of the literature, the effectiveness of nootropics in this indication. The analysis was limited to nootropics with cholinergic activity, in view of the role played by acetylcholine in learning and memory. Acetylcholine was the first neurotransmitter identified in the history of neuroscience and is the main neurotransmitter of the peripheral, autonomic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 45 publications
1
27
0
3
Order By: Relevance
“…Furthermore, GPE significantly enriched Ach content, in a concentration dependent manner, supporting the nootropic properties of the compound. To note, improved learning and memory has been widely associated with an enhancement in cholinergic neurotransmission in the hippocampus [14,[26][27][28]. Our data suggested an augmentation of Ach that could be beneficial for memory consolidation in neurons.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Furthermore, GPE significantly enriched Ach content, in a concentration dependent manner, supporting the nootropic properties of the compound. To note, improved learning and memory has been widely associated with an enhancement in cholinergic neurotransmission in the hippocampus [14,[26][27][28]. Our data suggested an augmentation of Ach that could be beneficial for memory consolidation in neurons.…”
Section: Discussionsupporting
confidence: 52%
“…In particular, reduced levels of PC and/or PUFAs in brain cells have been associated to a decrease in membrane excitability and neurotransmitter release [4,5] that lead to insufficient synaptic transmission and finally to memory impairment. Consistently, the administration of drugs able to restore membrane composition and functionality can ameliorate memory performances [14]. Among these compounds, GPE has emerged in preserving the well-being of astrocytes and neural stem cells [1,4,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Являясь источником холина и фосфолипидов, лецитин принимает участие в синтезе ацетилхолина, строении нейрональных мембран и миелина. Исследователи выдвигают гипотезы и предполагают, что лецитин улучшает когнитивные функции [59,60]. Доклинические исследования показали, что лецитин достоверно повышает уровень важного для когнитивных функций нейромедиатора ацетихолина [61].…”
Section: педиатрическая фармакологияunclassified
“…This was followed by a series of cerebral circulation enhancers with primarily vasodilating action. Unfortunately, these drugs were quite inefficient and led to a period of neurocentric research with the discovery of nootropic substances, which showed a certain level of efficacy to slow cognitive decline in vascular dementia (Colucci et al 2012). Animal models and brain imaging techniques allowed the discovery of several risk factors and mechanisms involved in the development of vascular cognitive impairment.…”
mentioning
confidence: 99%